Health and Climate Benefits of Heat Adaptation Strategies in Single-Family Residential Buildings - Williams, Augusta A.; Baniassadi, Amir; Izaga Gonzalez, Pablo; Buonocore, Jonathan J.; Cedeno-Laurent, Jose G.; Samuelson, Holly W. (Frontiers in Sustainable Cities, 2020)
As the frequency and severity of extreme heat increases with global climate change, residential buildings play a key role in defining personal temperature exposures. In recent decades, residential buildings have become the focus of energy efficiency and cost savings programs and initiatives. Residential buildings can also mitigate high indoor temperatures and heat-related health impacts, but these heat adaptation interventions have not been fully evaluated for their potential energy, climate, and health benefits. We aimed to quantify the health and climate benefits of energy and indoor temperature reductions that result from heat adaptation strategies applied to residential (specifically single-family detached built between 1990-2010) buildings in 10 U.S. cities. Building energy models were used to simulate energy reduction retrofits, including changing roof reflectivity, adding window overhangs, improving window properties, and roof/wall insulation, as well as the addition of shade trees and indoor phase change materials. We used the building simulation results to estimate attendant reductions in greenhouse gas (GHG) and criteria air pollution (AP) emissions from the electrical grid, and used the damage estimates to evaluate the resulting climate and health benefits. Under light and deep retrofit scenarios respectively, we estimate that the simulated heat adaptation retrofits in this subset of relatively new buildings have the potential to yield $1.10 or $1.57 billion in direct utilities savings. There is an additional $462.9 million ($301.3 - $909.9 million) or $692.8 million ($442.6 million - $1.385 billion) in climate and health benefits, due to avoided GHG and AP emissions. Put simply, the climate and health benefits may account for an additional 42-44% of the direct utility savings, on average. Climate and health benefits were generally highest for adaptations simulated in hot climates (Dallas, TX and Houston, TX) or in areas with dirtier fuel mixes (Chicago, IL and Philadelphia, PA). When climate and health savings are included, the payback periods of these interventions can decrease by nearly half. We also discuss the potential additional health benefits of reducing indoor temperatures during extreme heat. These significant savings from avoided climate and public health damages should be factored into climate adaptation decision making by stakeholders and policymakers.